THE CONCEPT AND ESSENCE OF INVENTORIES IN THE LOGISTICS SYSTEM OF AN ENTERPRISE - REZNIK NADIІA; CHORNENKA, LIUDMYLA; TYRINOV, ANDRIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
This article describes the concepts: inventories, strategic inventories, the meaning and essence of inventory management system, the reasons for the creation of inventories. Inventories in one form or another are present along the entire length of the logistics chain, both in production and in circulation. The article summarizes the general characteristics of models and methods of inventory management. It is determined that, in general, inventories are a form of material flow, a crucial marketing tool and a strategic means of improving competitive positions in the commodity market. The main function of inventories is to ensure the continuity of the process of social reproduction. At all stages of the cycle of resources and products of labor, material (commodity) flows act as one or another inventory. It is substantiated that inventories occupy a special place in the property and dominant positions in the cost structure of enterprises in various fields in determining the results of economic activity of the enterprise and in covering information about its financial condition. It is noted that an important aspect is the need to create inventories in logistics systems and maintain inventory levels at such a level to ensure uninterrupted supply of all units with the necessary material resources, provided compliance with the cost-effectiveness of the entire process of material flow. The purpose of this article is to study the term “inventories” and the main features of the category of inventories based on an analysis of the approaches of various scientists to this question. In the logistics system of a manufacturing enterprise, one of the objects of management is the flow of inventory, which is presented in the form of inventories. Inventories began to be seen as a form of material flow that has its limits in time and space.